Genome scan linkage analysis identifies a major quantitative trait loci for fatty acid composition in longissimus dorsi muscle in an F2 intercross between Landrace and Korean native pigs - Park, Hee-Bok; Han, Sang-Hyun; Yoo, Chae-Kyoung; Lee, Jae-Bong; Kim, Ji-Hyang; Baek, Kwang-Soo; Son, Jun-Kyu; Shin, Sang-Min; Lim, Hyun-Tae; Cho, In-Cheol (Animal bioscience, 2017)
OBJECTIVEThis study was conducted to locate quantitative trait loci (QTL) influencing fatty acid (FA) composition in a large F2 intercross between Landrace and Korean native pigs.METHODSEighteen FA composition traits were measured in more than 960 F2 progeny. All experimental animals were genotyped with 165 microsatellite markers located throughout the pig autosomes.RESULTSWe detected 112 QTLs for the FA composition; Forty seven QTLs reached the genome-wide significant threshold. In particular, we identified a cluster of highly significant QTLs for FA composition on SSC12. QTL for polyunsaturated fatty acid on pig chromosome 12 (F-value = 97.2 under additive and dominance model, nominal p-value 3.6×10-39) accounted for 16.9% of phenotypic variance. In addition, four more QTLs for C18:1, C18:2, C20:4, and monounsaturated fatty acids on the similar position explained more than 10% of phenotypic variance.CONCLUSIONOur findings of a major QTL for FA composition presented here could provide helpful information to locate causative variants to improve meat quality traits in pigs.